2016
DOI: 10.1007/s11427-015-4997-y
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD

Abstract: We characterized a unique group of patients with neuromyelitis optica spectrum disorder (NMOSD) who carried autoantibodies of aquaporin-4 (AQP4) and myelin-oligodendrocyte glycoprotein (MOG). Among the 125 NMOSD patients, 10 (8.0%) were AQP4-and MOG-ab double positive, and 14 (11.2%) were MOG-ab single positive. The double-positive patients had a multiphase disease course with a high annual relapse rate (P=0.0431), and severe residual disability (P<0.0001). Of the double-positive patients, 70% had MS-like brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
3
44
0
2
Order By: Relevance
“…As some patients with NMO are MOG‐IgG‐positive, it is interesting to know if there are cases doubly positive for MOG‐IgG and AQP4‐IgG. In most recent studies with MOG‐IgG‐CBA, no patients possessed both MOG‐IgG and AQP4‐IgG, but some doubly positive cases have been reported …”
Section: Cba To Detect Mog‐iggmentioning
confidence: 99%
See 1 more Smart Citation
“…As some patients with NMO are MOG‐IgG‐positive, it is interesting to know if there are cases doubly positive for MOG‐IgG and AQP4‐IgG. In most recent studies with MOG‐IgG‐CBA, no patients possessed both MOG‐IgG and AQP4‐IgG, but some doubly positive cases have been reported …”
Section: Cba To Detect Mog‐iggmentioning
confidence: 99%
“…In most recent studies with MOG-IgG-CBA, no patients possessed both MOG-IgG and AQP4-IgG, but some doubly positive cases have been reported. 22,23 Clinical, magnetic resonance imaging and laboratory features…”
Section: Cba To Detect Mog-iggmentioning
confidence: 99%
“…Çin'de yapılan bir çalışmada, 125 NMOSD tanılı hastanın 10'unda çifte pozitiflik saptanmış. Bu hastalarda yıllık relaps oranının yüksek olduğu ve kalıcı sakatlığa yol açtığı bildirilmiş (19) . Çalışmamızda, hastanın da ortalama yılda bir atağı olmakla birlikte, halen sekelsiz izlenmektedir.…”
Section: Discussionunclassified
“…These immune cells have been demonstrated to be involved in the initiation, progression and resolution of multiple sclerosis (MS). In this issue, Yan et al reported a unique group of patients with neu-romyelitis optica spectrum disorder (NMOSD) who carried autoantibodies of aquaporin-4 (AQP4) and myelin-oligodendrocyte glycoprotein (MOG) (Yan et al, 2016). They found NMOSD patients carrying both anti-AQP4 and anti-MOG antibodies exhibited combined features of prototypic NMO and relapsing-remitting form of MS, whereas NMOSD with only anti-MOG antibody exhibited an "intermediate" phenotype between NMOSD and MS, indicating that anti-MOG antibody might be pathogenic in NMOSD patients and that determination of anti-MOG antibody may be instructive for management of NMOSD patients.…”
mentioning
confidence: 99%